Black Truffles Affect Quercus aliena Physiology and Root-Associated nirK- and nirS-Type Denitrifying Bacterial Communities in the Initial Stage of Inoculation - Kang, Zongjing; Li, Xiaolin; Li, Yan; Ye, Lei; Zhang, Bo; Zhang, Xiaoping; Penttinen, Petri; Gu, Yunfu (Frontiers in Microbiology, 2022)
Truffles (Tuber spp.) are edible ectomycorrhizal fungi with high economic value. Bacteria in ectomycorrhizosphere soils are considered to be associated with the nutrient uptake of truffles and hosts. Whether Tuber spp. inoculation can affect the growth of Quercus aliena, the ectomycorrhizosphere soil and the rhizosphere nirK and nirS-denitrifier communities at the ectomycorrhizae formation stage is still unclear. Therefore, we inoculated Q. aliena with the black truffles T. melanosporum and T. indicum, determined the physiological activity and morphological indices of Q. aliena seedlings, analyzed the physicochemical properties of ectomycorrhizosphere soils, and applied DNA sequencing to assess the nirK and nirS- denitrifier community structure in ectomycorrhizosphere soils. Peroxidase activity was higher in the seedlings inoculated with T. melanosporum than in the T. indicum inoculation and not inoculated control treatments. The available phosphorus contents were lower and nitrate contents higher with than without truffle inoculation, and T. melanosporum treatment differed more from the control than the T. indicum treatment. The richness of the nirK-community was highest in the T. indicum treatment and lowest in the not inoculated treatment. The differences in nirK-community composition across treatments were not statistically significant, but the nirS communities were different. The nirS-type bacteria correlated with three environmental factors (pH, available phosphorus and nitrate contents) whereas the nirK-type bacteria was associated with the nitrate contents only. Generally, this work revealed that inoculation with Tuber spp. would change a few nutrient contents and richness of nirK-type bacteria. And had little effects on growth of Q. aliena seedlings in the initial stage of inoculation. The results may provide in-depth insights into the relationships between Tuber spp. and hosts, which should be taken into account when developing truffle production methods.